Characterizing medication discrepancies among older adults during transitions of care: a systematic review focusing on discrepancy synonyms, data sources and classification terms. (October 2013) - Kostas, Tia; Paquin, Allison M; Zimmerman, Kristin; Simone, Mark; Skarf, Lara M; Rudolph, James L
Medication reconciliation is a Joint Commission National Patient Safety Goal prioritized at transitions of care. Medication discrepancies are the reason for, and result of, medication reconciliation. However, their characterization in the literature has not been systematically studied. Older adults are at particularly high risk for medication discrepancies given the prevalence of polypharmacy in this population. The aim was to determine how medication discrepancies among older adults are defined during transitions of care by analyzing synonyms, medication data sources and classification terms. A systematic search of PubMed and EMBASE for primary literature involving medication discrepancies among adults aged ≥50 years during hospital care transitions was carried out. Reviewers consolidated data into like categories and used descriptive statistics to summarize findings. Out of 746 records retrieved, 35 studies were included in this review. In total, 19 studies (54%) were exclusive to adults over 65 years of age. Study settings included hospital discharge (n = 16; 46%), admission (n = 13; 37%) and mixed or multiple transitions (n = 6; 17%). Synonyms for discrepancies included inconsistencies, incongruences, inaccuracies and disagreements, among others. Common data sources included inpatient medication records and medication histories. A comprehensive, best possible medication history utilizing all available medication data sources was recorded in 51% of studies (n = 18), most consistently at admission. Most studies (n = 32; 91%) classified discrepancies; common classification terms included drug dose (n = 28; 88%), omission (n = 26; 80%) and commission (n = 16; 50%). In this first systematic review of medication discrepancy definitions, we found inconsistency across studies. Standardization and common discrepancy nomenclature is necessary for medication reconciliation outcomes to be compared, and to identify best practices to enhance safety. Safety implications are most salient in older adults given the number of medications and transitions of care to which they are exposed, as well as their sensitivity to adverse consequences of medication discrepancies.